Coronary Heart Disease and Cardiovascular Risk Factors in Patients With Idiopathic Inflammatory Myopathies: A Systemic Review and Meta-Analysis - Qin, Li; Li, Fang; Luo, Qiang; Chen, Lifang; Yang, Xiaoqian; Wang, Han (Frontiers in Medicine, 2022)
Objectives: It is well-established that the association between atherosclerotic cardiovascular diseases (ASCVD) and connective tissue diseases (CTDs), but the relationship between coronary heart disease (CHD) and idiopathic inflammatory myopathies (IIMs) remains controversial yet. The aim of this meta-analysis is to systematically evaluate the risk of CHD in IIMs patients. In addition, we explore differences in traditional cardiovascular risk factors between IIMs patients and controls. Methods: We searched Pubmed, EMBASE and Cochrane databases to identify relevant observational studies published in English up to August 2021. Pooled relative risk (RR) and 95% confidence interval (CI) was calculated using the generic inverse variance method for the risk of CHD. A meta-proportion analysis was conducted to assess differences in cardiovascular risk factors between two groups. Results: A total of 15 studies met inclusion criteria: 7 studies focused on CHD and 9 studies focused on traditional cardiovascular risk factors. The results demonstrated that IIMs patients had a higher risk of CHD (RR=2.19, 95% CI: 1.40-3.42). Hypertension (OR=1.44, 95% CI: 1.28-1.61), diabetes mellitus (OR=1.67, 95% CI: 1.55-1.81) and dyslipidemia (OR=1.48, 95% CI: 1.19-1.84) were more prevalent in IIMs patients compared with controls. However, there was a significant heterogeneity among studies assessing the risk of CHD and hypertension. Subgroup analysis demonstrated that definition of CHD, country and sample size may be potential sources of heterogeneity. Conclusions: IIMs patients were at increased risk of CHD, and traditional cardiovascular risk factors appeared more prevalent in IIMs patients. This systemic review offers the proof that early appropriate interventions could reduce cardiovascular-associated morbidity and mortality in IIMs patients.